The Influence of Marketing Mix and Customer Satisfaction on the Increase of Sales Revenue at Grand Optic Surabaya - Shinta Ardhia, Unitassia; Hafidulloh, Hafidulloh; Haryati, Endri; Amelia Shinta, Ria (UMSurabaya Publishing, 2025)
This study aims to analyze the influence of Marketing Mix (Product, Price, Place, and Promotion) on Customer Satisfaction and its impact on Grand Optik Sales Turnover. The research method uses a quantitative approach with a purposive sampling technique, involving 120 respondents. Data analysis was conducted using multiple linear regression and the Sobel test to identify the role of Customer Satisfaction as an intervening variable . The results showed that Price and Place have a significant effect on Customer Satisfaction, while Promotion has a negative effect. In addition, Customer Satisfaction is proven to be a significant mediating variable in the relationship between Marketing Mix and Sales Turnover. The implications of this study emphasize the importance of marketing strategies that focus on improving product quality, competitive price adjustments, distribution optimization, and more effective promotions to increase customer satisfaction and sales turnover.